Strategi Peningkatan Daya Saing UKM Sektor Sapi Perah di Indonesia - Rahmawati, Siti; Kartika, Lindawati; Syamsun, Muhammad; Sayekti, Andita (Jurnal Aplikasi Manajemen, 2016)
This study aimed to identify theperception of farmers to the compensation system, workplace culture, work engagement, and competencies;to identify the compensation system is based on a points system; and to determine the effect of compensation, workplace culture, work engagement, and competence on the competitiveness of the SMEs sectorof Dairy Cattle.This study was conducted at seven locations,namely, Bandung, Bogor, Malang, Yogyakarta, and Boyolali in early March until the end of July 2016. This study was conducted by quantitative and qualitative descriptive approach. The method of this study was the compensation analysis based on a points systemand PLS SEM. Sample selection has been done by purposive sampling method with a total 202 farmers. The results showed thatfactors affecting the improvement of the competitiveness of the SMEs sector is thedairy cow compensation and work engagement. To improve the compensation system has been applied to the SMEs sector of Dairy Farmers then in decision making in the conduct of salary to workers cattle can be based on nine factors worthy of compensation, such as work experience, skills, visual skills, social skills, responsibility for the equipment, responsibilities another initiative, physical condition and physical effort. Compensation system could be improved to better leads to the competitiveness of the SMEs sector of Dairy Farmers. Then for the work factor can be enhanced by engagement of internal livestock workers through full engagement in work, so that workers can feel more committed in doing their jobs as farmers,so that creates a sense of dedication to the job. That will affect the resulting performance and may affect to the competitiveness of the SMEssector of Dairy Cattle.Â